SYMBOLIC MEANING OF LAMOHOLOT’S TRADITIONAL ARCHITECTURE IN ILE APE, LEMBATA ISLAND, EAST NUSA TENGGARA - Dionisius Kumhan; Agus Saladin; Enny Supriati Sardiyarso (International Journal on Livable Space, 2016)
AbstractBesides climate, economic, politic, social and cultural factors, belief/religion factor has an influence on the shape and meaning of traditional house. Lamaholot tribe’s traditional house in Ile Ape, Lembata Island is rich of architectural symbolism. The relation between the shape and the physical symbolic meaning willbe described in this articles. Through qualitative approach, it isfound that the space structure of Lamohot’s traditional house is the manifestation of social stratifications status and community’s belief system, both horizontally and vertically.Keywords: Shapes, meaning, architecture elements of traditional house, Lamaholot tribe.